Chronic kidney disease and progression factors in patients with type 2 diabetes mellitus - Daniel Batista Téllez; José Carlos Estrada Hernández; Leobel Morell Pérez (Revista Información Científica, 2024)
Introduction: chronic kidney disease is an aggravating condition for the public health system. The detection and timely monitoring of the triggering and progression factors of the disease are a priority in each health system.